Utilisation of staff clinic facility in a Northwest Nigeria hospital: emerging challenges for the National Health Insurance Scheme - G. C. Michael; B. A. Grema; S. O. Yakubu; I. Aliyu (South African Family Practice)
Background: The health status of workers and their families affects workplace productivity. The National Health Insurance Scheme (NHIS) objective of improving healthcare accessibility to Nigerians has increased service utilisation but may pose new challenges to existing facilities. This study was undertaken to describe the pattern of clinic utilisation, disease entities of subjects, use of the excused-duty certificate and identify points of delay